The Impact of Boredom in Marriage on Marital Satisfaction - Muturi, Elizabeth (International Journal of Psychology, 2023)
Purpose: The aim of the study was to investigate the impact of boredom in marriage on marital satisfaction. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low-cost advantage as compared to field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Boredom in marriage can influence the spouses' behaviors, emotions, and cognitions, such as reducing their positive interactions, increasing their negative interactions, lowering their mood, and impairing their judgment. Boredom in marriage can have negative consequences for the individual and relational well-being of the spouses, such as affecting their physical and mental health, undermining their intimacy and commitment, and increasing their risk of infidelity or divorce. Boredom in marriage can be prevented or reduced by enhancing the quality and quantity of communication, sharing new and meaningful experiences, expressing appreciation and affection, seeking professional help if needed, and maintaining a positive attitude and outlook on the relationship. Unique Contribution to Theory, Practice and Policy: The Arousal Theory, Cognitive Theory and Psychodynamic Theory may be used to anchor future studies on use of marriage institutions. Marital therapists and counselors could incorporate boredom assessment and intervention strategies in their work with couples who report low marital satisfaction. Policymakers and educators could design and implement programs that promote healthy and satisfying marriages in the society.